PENGARUH ALIRAN KAS INTERNAL DAN KEPEMILIKAN MANAJER DALAM PERUSAHAAN TERHADAP PEMBELANJAAN MODAL: MANAGERIAL HYPOTHESES ATAU PECKING ORDER HYPOTHESES? 1) - Sartono, Agus (Journal of Indonesian Economy and Business, 2001)
This paper aimed to test the two agency-based arguments that known as the âpeckingâ order hypotheses and âmanagerialâ hypotheses at the Jakarta Stock Exchange. Pecking order hypotheses says that manager choose the level of capital expenditure that maximizes the wealth of current shareholders, regardless of the managersâ ownership stake in the firm. According to the managerial hypothesis, manager who have small ownerships take in the firm use internal cash flow to under take a level of capital expenditures higher than that which would maximize the wealth of other current shareholders. Testing on 223 firms that chosen based purposive sampling found there is weak association between capital expenditure and internal cash flow, either between capital expenditure and insider ownership. Overall, the results favour the pecking order hypotheses.Â Keywords: Pecking Order Hypotheses, Managerial Hypotheses, Capital Expenditure, Insider Ownership, Internal Cash flow